Research on Film Marketing in the New Media - Lyu Kunhang (SHS Web of Conferences, 2024)
New media, as an important information revolution in Internet technology, has promoted the innovative development of traditional marketing models and marketing concepts. As film marketing navigates this transition from traditional methodologies to those informed by new media dynamics，it concurrently experiences accelerated trajectories and intricate challenges. This research aims to elucidate the nuanced transformation of film marketing strategies within the new media landscape, employing the case study methodology for an in-depth exploration.